Potencialização do acontecimento e racionalidade patêmica nos discursos sobre os refugiados sírios: a hipótese do ápice midiático - Garcia, Adriana Domingues (2020)
This research analyzes the discursive strategies of the constructions of reality in the media approaches about the event of the Syrian refuge. Specifically, we identified pathemic discursive strategies, mapped the self-made formation observatory networks that constitute the social system, in addition, we verified the relations of media events and their issues of territoriality and contributed to the studies that work the relations between media and emotional discourses. The selection of the corpus was carried out within the criteria of observing discursive regularity, based on events that marked the recent history of Syrian refugees, which aroused public debate, identified in the news involving dead or injured children. Four communicational episodes were chosen (BRAGA, 2013): a) Aylan Kurdi; b) Zaid Abdul; c) Omran Daqeenesh; and d) Aya and Ahmed al-Yousef, published in the digital newspapers Folha.com, Euronews, Al Jazeera and The New York Times. The adopted methodology was the Emotive Discourse Analysis, by Patrick Charaudeau (2007) and Textual Discursive Analysis (ADT), through the Iramuteq Software. With the help of these tools, we identified three main analytical categories: “Qualifications”, “Compassion” and “Experience”. The analyzes revealed that refugees are viewed in a negative way, in general, and their adjectives refer to the inferiorization of the individual, not only in terms of vulnerability and victimization, but also as an invader, fugitive and threat. In addition, we verified the recurrence meant the intention to raise public awareness with the discursive construction of the “Refugee Crisis”. We highlight the newspapers' self-referential strategy in justifying the use of children's images, showing behind the scenes of the news and, above all, personalizing the event, creating and discursively supporting the designation of names to be representatives of each episode, icons and symbols of the macro event. This dynamics, which we call episodialization, is one of the propelling springs of the logic of the media apex hypothesis, because, together with all the elements of “pathemic rationalization”, it is configured as a communicative process self-fortified by intrasystemic relationships, through self-referentiality, essentially found in the category “Experience”, heteroreferentiality, with the resource of reentry (remissions) and reference to other social systems, mainly the political, cultural and religious. We believe that this set of socio-technological and discursive actions are the most efficient strategies for reaching news on a large scale and the worldwide reverberation of the Syrian refugee theme.